2020
DOI: 10.1097/md.0000000000020531
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of Jinhua Qinggan granule (JHQG) in the treatment of coronavirus disease 2019 (COVID-19)

Abstract: Background: Currently, the global number of infected novel coronavirus has exceeded 2.6 million and the death toll has exceeded 170,000, but the specific drug for the treatment of COVID-19 has been not appears. In the process of fighting COVID-19 in China, JHQG has been promoted by the Chinese government and widely used in the treatment of COVID-19. The purpose of this study is to systematically evaluate the efficacy and safety of JHQG for COVID-19.Methods: We are going to search the electronic databases: PubM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 15 publications
(12 reference statements)
0
14
0
Order By: Relevance
“…However, clinical studies have shown that it has therapeutic efficacy against viral infections. In 2011, a clinical trial with 403 patients was conducted to verify the effectiveness of Jinhua Qinggan and oseltamivir in treating H1N1 influenza [ 11 ]. This study showed that when compared to placebo, the combination of Jinhua Qinggan and oseltamivir shortened the time patients experienced a fever ( P < 0.001), with the fever time for patients in the combination group being 19% shorter than the oseltamivir group ( P = 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, clinical studies have shown that it has therapeutic efficacy against viral infections. In 2011, a clinical trial with 403 patients was conducted to verify the effectiveness of Jinhua Qinggan and oseltamivir in treating H1N1 influenza [ 11 ]. This study showed that when compared to placebo, the combination of Jinhua Qinggan and oseltamivir shortened the time patients experienced a fever ( P < 0.001), with the fever time for patients in the combination group being 19% shorter than the oseltamivir group ( P = 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Jinhua Qinggan granules Jinhua Qinggan granules are composed of honeysuckle, gypsum, ephedra (honey), bitter almond, baicalin, forsythia, fritillaria, burdock seed, artemisia annua, mint, and licorice [11]. Jinhua Qinggan has traditionally been used for the treatment of plague diseases.…”
Section: Application Of Oral Tcms In the Treatment Of Covid-19mentioning
confidence: 99%
“…In the combat against COVID-19, National Health Commission of China approved both LHQWC and JHQGG as clinical therapies in China, and observational studies showed that both can effectively relieve fever, fatigue, cough and phlegm in the early stage of COVID-19, contributing to reductions in risks of rapid clinical deterioration. Supportively, in vitro studies have revealed that both formulae have anti-inflammatory effects, providing fundamental evidence for clinical application of both formulae in the fight against COVID-19 Duan, 2020;Runfeng et al, 2020;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 95%
“…Of note, G. biloba , P. orientalis and L. japonica are frequently used TCMs for antiviral treatment. Remarkably, considerable research has indicated that extracts and formulas of L. japonica are effective for multiple coronaviruses including SARS-CoV-2 ( Hu et al, 2021b ; Zhang et al, 2020 ). Our findings suggested that these biflavones might act as antiviral ingredients of the above TCMs by inhibiting PL pro .…”
Section: Introductionmentioning
confidence: 99%